Biomaterials: Magnetic Levitational Assembly for Living Material Fabrication (Adv. Healthcare Mater. 10/2015). Issue 10 (July 2015) - Tasoglu, Savas; Yu, Chu Hsiang; Liaudanskaya, Volha; Guven, Sinan; Migliaresi, Claudio; Demirci, Utkan
<x xml:space="preserve">Abstract</x> Functional living materials with microscale compositional topographies are prevalent in nature. However, the creation of biomaterials composed of living micro building blocks, each programmed by composition, functionality, and shape, is still a challenge. On page 1469, S. Tasoglu, U. Demirci, and co‐workers present a powerful yet simple approach to create living materials using a levitation‐based magnetic method.